STEM Analysis (Science, Technology, Engineering and Mathematics) of the Agricultural System of the Indigenous People of Urug Village - Suci Siti Lathifah; Ari Widodo; Ida Kaniawati; Siti Sriyati (Jurnal Penelitian Pendidikan IPA, 2024)
This study examines the potential of STEM in the context of indigenous farming systems in Urug Village to improve agricultural sustainability, increase crop yields, and promote environmental conservation through education. Surveys and data collection to identify challenges and opportunities, and to develop solutions that meet the needs of indigenous communities while prioritizing sustainability and environmental conservation are practical steps for this study. Data was collected from the agricultural practices of the Urug indigenous community using the survey method, which included participatory observations, interviews, literature reviews, and documentation. Technical terms are explained upon first mention. The Urug indigenous community follows a series of rice planting procedures. These include babad susukan, seed preparation, seed soaking for two days, stocking, ngabaladah, babad, mingul, ngangler, tandur, ngoyos, ngadares, dibuwat (harvest), lantayan, and ngunjal. The study of science in the community centers around concepts such as astronomy, ecosystems, simple aircraft, pressure, temperature, and heat. Additionally, simple technologies such as terracing, etem, and leuit are employed. Agricultural engineering focuses on environmentally friendly rice farming. Mathematics deals with numbers and operations used in solving numeric problems, as in the calculation of the Pranatamangsa calendar and the Tandur. This agricultural knowledge can be integrated into STEM education.